Survei Penerapan Teori Behaviorisme Skinner Pada Pendidikan Karakter di Sekolah XYZ - Dwi Aning Apriandani HI; Eklesia Khesywania Gea; Yogi Widi Prasetyo; Yohanes Adi Saputra Abraham (Jurnal Ketopong Pendidikan, 2025)
Character education is an important aspect in shaping students' behavior and morals. This study aims to evaluate the application of B.F. Skinner's behaviorism theory in character education and analyze its influence on improving students' morals and ethics at XYZ High School. This study used a survey method with a quantitative approach to collect data from 34 students (55.74% of the population of 61 students) at XYZ High School Gading Serpong. The research instrument was a questionnaire with 15 statements measuring five character indicators: religiosity, nationalism, independence, mutual cooperation, and integrity, using a Likert scale of 1-5. Data were analyzed using a validity test (Cronbach's Alpha = 0.82), a normality test (p-value = 0.38), and a regression test. The results showed that the five character indicators had a positive and significant influence (F-count = 51.54 > F-table = 2.934) on students' character formation, with an average character index of 60% (high category). These findings indicate that the application of Skinner's operant conditioning theory through conditioning the school environment and forming repetitive habits has proven effective in improving students' morals and ethics. This study recommends the development of behaviorism-based character education, taking into account the challenges of the digital era and the influence of social media.